The bone labyrinth [compact disc, unabridged] : a Sigma Force novel - Rollins, James, 1961- (Rollins, James, 1961- Sigma Force novel., 2015)
Sigma Force Commander Gray Pierce makes paradigm-shifting discoveries about human evolution while investigating shadowy figures depicted in Neanderthal cave paintings.